2016
DOI: 10.1039/c5cc10555b
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in cell analysis of chemically synthesized histone H2A with multiple modifications

Abstract: The chemical synthetic route to histone H2A is described. An H2A-H2B dimer, histone octamer, and nucleosome were reconstituted with the synthetic H2A. Fluorescein-labeled H2A and multiply modified H2A, which has three different posttranslational modifications, were also synthesized, and applied to live-cell imaging and in vitro nucleosome stability assays, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The cysteine residue of the GGGYC peptide was modified with Alexa Fluor 488-maleimide in 25 mM 3-morpholinopropane-1-sulfonic acid (MOPS) buffer (pH 6.8) for 6 h at room temperature. The product, GGGYC–Alexa488 was purified by reversed phase high performance liquid chromatography (RP-HPLC, Jasco, Tokyo, Japan) and identified by matrix-assisted laser desorption and ionization time-of-flight mass spectrometry, as previously described 36 .…”
Section: Methodsmentioning
confidence: 99%
“…The cysteine residue of the GGGYC peptide was modified with Alexa Fluor 488-maleimide in 25 mM 3-morpholinopropane-1-sulfonic acid (MOPS) buffer (pH 6.8) for 6 h at room temperature. The product, GGGYC–Alexa488 was purified by reversed phase high performance liquid chromatography (RP-HPLC, Jasco, Tokyo, Japan) and identified by matrix-assisted laser desorption and ionization time-of-flight mass spectrometry, as previously described 36 .…”
Section: Methodsmentioning
confidence: 99%
“…The ability to synthesize an entire histone with SPPS and NCL has made it possible to investigate histone PTMs and their readers, writers, and erasers in a contextually accurate manner, both independently and in combinations. For example, the first report of a total synthesis of histone H2A demonstrated that known PTMs S1ph, K75me2, and K119Ac K119Ac PTMs do not dramatically effect nucleosome stability, individually [372] . A recent total NCL synthesis of H2AY57ph and H2BK120ub with subsequent nucleosome formation revealed that the Y57ph mark inhibits de‐ubiquitylation of K120ub by the SAGA) complex [373] .…”
Section: Synthetic Histonesmentioning
confidence: 99%
“…For example, the first report of a total synthesis of histone H2A demonstrated that known PTMs S1ph, K75me2, and K119Ac K119Ac PTMs do not dramatically effect nucleosome stability, individually. [372] A recent total NCL synthesis of H2AY57ph and H2BK120ub with subsequent nucleosome formation revealed that the Y57ph mark inhibits de-ubiquitylation of K120ub by the SAGA) complex. [373] Similarly, the Okamoto group also synthesized a H2A with a Y57ph modification and reconstructed nucleosomes.…”
Section: Chemically Synthesized Histonesmentioning
confidence: 99%
“…In 2016, Okamoto and coworkers conducted the first chemical synthesis of a variety of post-translationally modified histones H2A through Fmoc based SPPS and sequential NCL utilizing N- acylurea chemistry (Hayashi et al, 2016 ). H2A was divided into three peptide segment and the N-terminal cysteine of segment H2A (47–85) was temporarily protected with thiazolidine (Thz) to avoid self-ligation.…”
Section: The Total Chemical Synthesis Of H2a With Ptmsmentioning
confidence: 99%